Family planning knowledge, use, and associated factors among women with mental illness and epilepsy in Rwanda: a cross-sectional study - Pacifique Mukangabire; M. Providence Umuziga; Benoite Umubyeyi; Benoite Umubyeyi; Donatilla Mukamana; Darius Gishoma; Vedaste Baziga; Philomene Uwimana; Fidele Sebera; Olive Bazirete; Clementine Kanazayire (Frontiers Media S.A., 2024)
IntroductionFamily planning knowledge and access to quality family planning services occupy a central position in the lives of all women of reproductive age. However, women with mental illness and epilepsy who are at a high risk of sexual violence, unwanted pregnancies, poor obstetric outcomes, and drug interaction consequences, need it the most. Understanding their family planning knowledge and utilization remains crucial for meeting their needs. The present study aims to assess knowledge, use of family planning, and associated factors among women living with mental illness and epilepsy who attend the Ndera Neuropsychiatric Hospital and affiliated branches.MethodologyA cross-sectional study was conducted between October 2022 and February 2023. The study involved a purposive sample of 289 women who attended the Ndera Neuropsychiatric Hospital and its two affiliated branches during the data collection period. Psychiatric nurses administered a structured questionnaire. Data were analyzed using descriptive statistics, and multiple logistic regression analysis was performed to assess the factors associated with the use of family planning methods.ResultsOut of 289 who participated in the study, the majority (96.9%) were aware of family planning methods, most (67.8%) had used one method once in their life course, a half (51.9%) were using a family planning method at the time of data collection, and a slight number (26%) expressed intentions of using a family planning method in the future. The most known and used methods were respectively the injectable (17.5%) and oral contraceptive pill (17.5%). Regarding the natural family planning methods, breastfeeding and withdrawal were less used. Being single (AOR = 66.4, 95% CI: 9.8, 44) or married (AOR = 51.4, 95% CI: 11.9-22), having a primary level of education (AOR = 5.6, 95% CI: 2.0, 15.9), knowing a contraceptive method (AOR = 5.8, 95% CI: 0.6, 49) and suffering from brief psychotic disorders (AOR = 2.7, 95% CI: 1.1, 6.6) predicted a higher utilization of family planning.ConclusionMost of the women with mental illness in this study were aware of family planning methods and had used one of the family planning methods in life. The national average is below when it comes to family planning awareness. It is important to improve family planning education and counseling for women who attend psychiatric outpatient clinics.